Relational ontology of money and ontic-institutional currency regimes: Phenomenologies and performativity of global liquidity in a hierarchical international monetary order - Buz, Andrii (Здобутки економіки: перспективи та інновації, 2025)
The study explores the relational ontology of money and the ontic-institutional character of currency regimes to clarify how global liquidity functions within a hierarchical international monetary order. The purpose is to integrate philosophical and institutional perspectives on money by analysing it not as a material object, but as a dynamic social relation grounded in collective acceptance and institutionalised credit structures. The research applies an interdisciplinary methodology, combining conceptual analysis in social ontology with a review of contemporary literature in international political economy and monetary theory. The results demonstrate that money is constituted through belief-dependent credit-debt relations, while currency regimes represent institutional facts sustained by legal frameworks and organised authority. Global liquidity emerges as both a phenomenological experience – manifested in credit cycles, financial volatility, and cross-border capital flows – and a performative outcome shaped by central bank interventions and institutional signalling. These mechanisms reinforce structural asymmetries, positioning certain key currencies, particularly the U.S. dollar, at the centre of the global system. The conclusions emphasise that international monetary stability relies on both credible institutional design and sustained collective intentionality. Addressing unequal access to liquidity and emergency monetary support requires reconsideration of current currency hierarchies and global monetary governance frameworks, suggesting the need for further research and institutional reform.